2003
DOI: 10.1136/gut.52.7.1030
|View full text |Cite
|
Sign up to set email alerts
|

Ten year incidence of HCV infection in northern Italy and frequency of spontaneous viral clearance

Abstract: Background: Little is known of the incidence of hepatitis C virus (HCV) infection, and the frequency of spontaneous viral clearance in the general population is unknown. We conducted an epidemiological study in two Apennine towns in northern Italy. Methods: Anti-HCV (ELISA and RIBA third generation) and HCV-RNA by polymerase chain reaction were tested in thawed sera from an adult general population of Loiano-Monghidoro in 1986 and 1996, obtained in the context of the MICOL (Multicenter Italian Study on Choleli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…The median age was 55.7 years (range 23-78 years). Three hundred and sixty-one patients In the present study, the overall prevalence of HCV infection found in lymphoproliferative disorders was not dissimilar from that observed in the general population from the same geographical area by Mazzeo et al (5.8% vs. 5.4%) [8]. However, among all types of lymphoproliferative disorders reported, MZL and DLBCL accounted for the vast majority of the cases (42/55, 76.4%).…”
Section: Prevalence Of Hepatitis C Virus Infection Among Patients Witcontrasting
confidence: 45%
“…The median age was 55.7 years (range 23-78 years). Three hundred and sixty-one patients In the present study, the overall prevalence of HCV infection found in lymphoproliferative disorders was not dissimilar from that observed in the general population from the same geographical area by Mazzeo et al (5.8% vs. 5.4%) [8]. However, among all types of lymphoproliferative disorders reported, MZL and DLBCL accounted for the vast majority of the cases (42/55, 76.4%).…”
Section: Prevalence Of Hepatitis C Virus Infection Among Patients Witcontrasting
confidence: 45%
“…Rarely individuals have viraemia with intermittently undetectable levels of HCV antibodies. 23,24 Others reported 0.2–0.9% of anti-HCV-negative organ donors were HCV-RNA-positive in France and the USA, 25,26 and 7 of the 232 mothers in the parent cohort who were HCV-RNA-positive did not have detectable anti-HCV. 10 …”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Genotype 1b is prevalent, particularly among transfused patients; genotype 2 is frequent in community acquired cases, especially in Southern Italy, while the proportion of genotypes 1a, 3, and 4 depends on the prevalence of drug abuse in a given area. These patterns and their fluctuations are the result of important socio-sanitary events recorded in the past decades, such as: the disappearance of post transfusion hepatitis C; improvement in sanitation policies which reduced the risk of community acquired hepatitis 32 ; spread of IVDA which caused an epidemic of viral hepatitis among young adults, especially in the Northern urban areas between the mid 1970s and the mid 1980s 34 ; and unsafe sexual behaviours and frequent travel to highly endemic areas of the far East, 35 which promoted the circulation of genotypes different from 1b and 2.…”
Section: Discussionmentioning
confidence: 99%